2022
DOI: 10.3390/mi13111875
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Filler Materials on Wettability and Mechanical Properties of Basalt/E-Glass Woven Fabric–Reinforced Composites for Microfluidics

Abstract: This paper presents the development of novel hybrid composites in the presence of filler particles and manufactured using a proposed new fabrication technique. The hybrid composites were fabricated using a basalt and E-glass woven fabric–reinforced epoxy resin matrix combined with graphite powder nanoparticles. Six sets of samples were fabricated using the vacuum-assisted free lamination compression molding technique. After the fabrication, wettability, mechanical properties (tensile, flexural and impact prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The fabrication of microfluidic devices requires an understanding of material properties and manufacturing techniques that can be used to create structures with desired characteristics. Atmakuri et al [ 4 ] explored the effect of filler materials on the wettability and mechanical properties of basalt/E-glass woven fabric-reinforced composites, which could be used to create microfluidic devices with high mechanical strength and tunable wettability. They found that the incorporation of graphite improves both the hydrophobicity and mechanical properties of the composites.…”
Section: Fabrication Of Microfluidic Devicesmentioning
confidence: 99%
“…The fabrication of microfluidic devices requires an understanding of material properties and manufacturing techniques that can be used to create structures with desired characteristics. Atmakuri et al [ 4 ] explored the effect of filler materials on the wettability and mechanical properties of basalt/E-glass woven fabric-reinforced composites, which could be used to create microfluidic devices with high mechanical strength and tunable wettability. They found that the incorporation of graphite improves both the hydrophobicity and mechanical properties of the composites.…”
Section: Fabrication Of Microfluidic Devicesmentioning
confidence: 99%
“…A study by Lapena et al [14] reported that basalt fiber-glass fiber hybridization increased tensile strength by 45% and interlaminar shear strength by 11%. A study by Atmakuri et al [15] on hybridization with basalt, E-glass, and graphite reported that hybrid fillers are better than single fibers. Also, they reported that basalt fibers have higher strength than glass fibers.…”
Section: Introductionmentioning
confidence: 99%